Causes and effects of the global decrease in demand - Milenko Krajisnik (UTMS Journal of Economics, 2014)
The current economic crisis has been lasting too long, and particular examples of economic growth and unemployment reduction in some countries have not been the accelerator sufficient for the global recovery. The general level of demand is low, hence so are the investments, although the most powerful economic factors, i.e. the highly developed countries and transnational companies, have the capacities for new investment cycles. This work analyses the causes and effects of decrease in demand, as well as the options available for removal of those causes and revitalization of the effects. One of the main causes of decrease in demand in a long run is the asymmetrical distribution of income which has led to a reduction in purchasing power of a large number of consumers, high debt level and change in demand structure. An additional problem, which can be regarded also as a cause of decline in demand in the short run, is the austerity policy which is being implemented both where necessary and conditioned and where voluntary albeit not necessary. In order to overcome the problem, it is necessary to increase and maintain demand, first initially and then permanently, which is where the state plays an important role.
Keywords: E41; J2; G01; 330; economic crisis; demand; consumption; asymmetrical distribution; employment; investments